Trends in body size, diet and food availability in the Cook Islands in the second half of the 20th century - Ulijaszek, S (Elsevier, 2003)
The body size of adult Cook Islanders on Rarotonga for the years 1952, 1966 and 1996 has been increasing. The rate of increase in stature of women aged 20-39 years was 0.5 cm per decade across the period 1952-1966, and 0.8 cm per decade for the period 1966-1996. The rate of increase of weight in the 20-29 years age group was 0.6 kg per decade in period 1, and 7.3 kg per decade in period 2. In the age group 30-39 years, the rates were 3.2 kg per decade and 5.1 kg per decade respectively. Changing food availability for the period 1961-2000 is used to compare estimates of dietary energy availability with estimates of physiological energy requirements. There has been reduced availability of traditional staples, a likely reduction in consumption of fish, increased consumption of meat, and a decline in the availability of dietary fats and oils. Daily per capita energy intakes in 1952 and 1966 greatly exceed an hypothetical physiological maximum value for energy expenditure, suggesting a large positive energy balance in 1952 and an even greater one in 1966, both predisposing to weight gain. Although daily per capita energy availability in 1996 is similar to the hypothetical physiological maximum value for energy expenditure, it exceeds the measured level of energy expenditure at that time. It is speculated that excessive energy intake relative to requirement is more likely to predispose to positive energy balance and weight gain than decline in energy expenditure, although to a lower extent than in 1966 and 1952.